CANUE: A Theoretical Model of Pain as an Antecedent for Substance Use. Issue 5 (11th September 2020) - Ferguson, Erin; Zale, Emily; Ditre, Joseph; Wesolowicz, Danielle; Stennett, Bethany; Robinson, Michael; Boissoneault, Jeff
Abstract: Background: Pain and substance use are frequently comorbid and have been shown to exert bidirectional effects. Self-medication of pain and distress via substance use is common and can be understood via negative reinforcement, ultimately strengthening the pathway between pain to substance use over time. As such, a testable model of the potentially modifiable candidate mechanisms that underlie the pain to substance use pathway is needed. Purpose: This review proposes a testable model of pain as an antecedent to substance use to guide future research and inform clinical practice. Methods: An integrative review of current evidence regarding pain, substance use, and associated risk factors (i.e., negative affect, pain-related attitudes, negative urgency, and substance use outcome expectancies) was conducted. Results: The Catastrophizing, Anxiety, Negative Urgency, and Expectancy (CANUE) model highlights modifiable risk factors for self-medicating pain with substance use, including increased negative affect and maladaptive pain-related attitudes (i.e., pain catastrophizing, pain anxiety, and fear of pain), negative urgency, and substance-related outcome expectancies for pain relief and enhanced pain coping. Conclusions: Targeted behavioral and psychological interventions that address these factors may facilitate more adaptive pain-coping responses, thereby reducing the impacts of pain on substance use. Systematic research is needed to evaluate the validity and clinical utility of this model. Abstract : The Catastrophizing, Anxiety, Negative Urgency, and Expectancy (CANUE) model proposes a testable model of pain as an antecedent to substance use, highlighting modifiable risk factors to guide future research and clinical practice.